1996
DOI: 10.1093/geront/36.4.502
|View full text |Cite
|
Sign up to set email alerts
|

The Illinois Elder Abuse System: Program Description and Administrative Findings

Abstract: In this article we describe the Illinois statewide elder abuse social service program, which is unusual in its comprehensive approach to the assessment and documentation of reported cases of abuse and its extensive data monitoring system. Descriptive information on the number and types of cases of elder abuse reported to the system are presented, along with information on the amount of social work time and administrative effort spent on substantiating abuse reports and providing services. Financial exploitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…Regarding the MSCC outcome, previous research reported rates of reduced risk, lessened abuse, or partial/complete resolution from 56% to 84%, and rates of ongoing high risk or unresolved abuse between 16% and 44% (Cripps, 2001;Kurrle, Sadler, Lockwood, & Cameron, 1997;Lithwick et al, 2000;Neale et al, 1996;Vladescu et al, 2000;Wolf & Pillemer, 1989. This comparative means of evaluation lacks validity, since it was done across studies and programs with considerably different circumstances and research conditions.…”
Section: Analytic Planmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the MSCC outcome, previous research reported rates of reduced risk, lessened abuse, or partial/complete resolution from 56% to 84%, and rates of ongoing high risk or unresolved abuse between 16% and 44% (Cripps, 2001;Kurrle, Sadler, Lockwood, & Cameron, 1997;Lithwick et al, 2000;Neale et al, 1996;Vladescu et al, 2000;Wolf & Pillemer, 1989. This comparative means of evaluation lacks validity, since it was done across studies and programs with considerably different circumstances and research conditions.…”
Section: Analytic Planmentioning
confidence: 99%
“…The opportunity to execute a program intervention to alleviate elder mistreatment is contingent upon the ability of the program to retain clients. Similar to previous studies measuring the retention outcome (Lithwick, Beaulieu, Gravel, & Straka, 2000;Neale, Hwalek, Goodrich, & Quinn, 1996;Roberto, Teaster, & Duke, 2004;Wolf & Pillemer, 2000), retention in this study was measured as a dichotomous variable based on whether or not the client accepted any services (no = 0; yes = 1). Corresponding with the main program goal, MSCC refers to the extent that the substantiated mistreatment situation has been alleviated following social service intervention.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reports on service effectiveness describe the types of services provided and the likelihood of service acceptance (Anderson & Theiss, 1987;Blakely & Dolon, 1991;Eisenberg, 1991;Fiegener, Fiegener, & Mesaros, 1989; Illinois Department on Aging, 1987;Longres, 1991;McDaniel, 1989;Vinton,1991 ). Neale, Hwalek, Goodrich, and Quinn (1996) reported that the services most frequently refused by clients in the Illinois APS system were housing (53%), in-home assistance (46%), and mental health referrals (54%). Sengstock, Hwalek, and Petrone (1989) found that APS workers tend to provide different types of services to clients, depending upon the type of abuse or neglect from which they suffer.…”
mentioning
confidence: 99%
“…Victims of confinement or neglect received, on average, more services than did victims of other types of abuse, and victims of physical abuse received the fewest services. Examining data abstracted from Illinois APS caseworker files, Neale et al (1996) provided estimates of the amount of time workers spend on substantiated cases of abuse; the number of days substantiated cases were open; and also the number of services needed, provided, and refused. However, neither of these studies examined the degree to which services were effective in relieving the abuse or reducing the potential for future abuse.…”
mentioning
confidence: 99%